Study on the long-term performance of shield tunnel passing through the gas-bearing strata - He, Jie; Wei, Xiangyang; Yin, Mei (Underground Space, 2023)
When the shield tunnel passes through the gas-bearing strata, gas and water leakage may occur depending on the sealing performance of the segment joints. This process involves the complex multiphase seepage flow phenomenon in unsaturated soil. In this study, a fully coupled solid-liquid-gas model of the GIL Utility Tunnel was established to investigate the influence of the high-pressure gas on the mechanical properties of the tunnel segments and joints. The constitutive model of the Extended Barcelona Basic Model was implemented to simulate the effect of the seepage process on soil deformation. The results show that significant upward displacement occurred in the gas reservoir and its overlying strata, and the maximum displacement reached 30 mm. In addition, during the leakage of the gas and the water, an increase in the average soil effective stress was observed. It would induce a reduction in the suction and expansion of the yield surface. The tunnel tended to be stable from 20 years onwards, thus the soil deformation due to the water leakage only occurred at the early stage. In addition, the joint opening under the most unfavorable internal force combination was 0.69 mm, and the corresponding bolt stress was 119.5 MPa, which is below the yield limit. The results of this study help to understand the influence of high-pressure gas on tunnel safety and the sealing performance of the joints.
Keywords: Infolettre; Infolettre_Juin_2023